Modern Pathogenetic Mechanisms of Systemic Scleroderma - Botirbekov Abdurashid Nazarkulovich (Zien Journals, 2023)
Systemic scleroderma is a chronic and often progressive autoimmune inflammation of the connective tissue, characterized by fibrosis of the skin and internal organs, widespread vascular lesions with unknown etiology, and heterogeneous clinical manifestations. Systemic scleroderma is a violation of the synthesis and accumulation of collagen in the skin (scleroderma) and other internal organs, especially in the connective tissue of the lungs, gastrointestinal tract (gastrointestinal tract), heart and kidneys. Over time, patients develop signs of a progressive structural and functional impairment of blood vessels and internal organs due to fibrosis. This review article presents current data on the pathogenetic mechanisms of systemic scleroderma.
Keywords: Systemic scleroderma; antinuclear antibodies; cells